The exposure and time spent on various audio-visual media devices by children in Delhi, India - Anand, Bhavna; Reddy, Singam Lakshmi Narasimha; Meena, Satish Kumar; Roy, Manas Pratim (Indian Journal of Child Health, 2020)
Background: The advancement in the technology and availability of mobile devices has rendered children more vulnerable to audio-visual media devices. However, studies with a focus on the exposure of children to such devices are a handful, particularly from the developing countries. Objectives: This study investigates the exposure of children to various audio-visual media devices. Methods: This cross-sectional, questionnaire-based study included 354 children (56.5% boys and 43.5% girls) between 6 months and 12 years who came for a wellness visit or vaccination at a tertiary care hospital in New Delhi, India, from August 2016 to July 2017. The study questionnaire was adopted from Zero to Eight Common Sense Media 2013 nationwide survey (USA). Results: All study children had access to mobile devices (75% to smartphones, and 25% to ordinary mobile phones); 93.5% had access to television and 14.4% had access to computers. For television, the average daily screen time was >2 h in 38.4% of children. It was significantly more in the age group of 2–8 years, female gender, and urban background (p2 h/day. Conclusion: Many of the study children have daily screen time for more than 2 h, warranting the need of specific guidelines for optimal media usage by children, especially for developing countries like India.